Extended Hildebrand solubility approach applied to sulphadiazine, sulphamerazine and sulphamethazine in some {1-propanol (1) + water (2)} mixtures at 298.15 K (2023)
Extended Hildebrand solubility approach (EHSA) was applied in this research to analyse the equilibrium solubility of sulphadiazine, sulphamerazine and sulphamethazine in some {1-propanol (1) + water (2)} mixtures at 298.15 K. Reported experimental solubilities and some fusion properties of these drugs were used for EHSA calculations. A good predictive character of EHSA (with mean deviations lower than 4.0%) was found by using regular polynomials in order five when correlating the interaction parameter (W) and the Hildebrand solubility parameter of solvent mixtures free of drug (d1+2). Nevertheless, the predictive character of EHSA was almost the same as obtained when logarithmic drug solubilities (log x3) were correlated with d1+2 by using a fifth-degree regular polynomial. © 2018 Informa UK Limited, trading as Taylor & Francis Group